Basic & Clinical Endocrinology, - Greenspan, Francis S., Gardner, David G. (McGraw-Hill, 2004)
Endocrinology is an expanding science, with new concepts and ideas appearing in the literature almost daily. Thus, it is imperative to have available a reliable source of information that keeps abreast of this mass of new knowledge. Basic & Clinical Endocrinology is just that type of resource. In this seventh edition, internationally recognized and outstanding specialists in each area of endocrinology have reviewed the new pathophysiologic concepts and treatments in their individual fields to bring the text up to date. The Introduction (Chapter 1) provides an excellent overview of the field. The basics of hormone synthesis, release, and action, as well as the important area of endocrine autoimmunity, are reviewed and updated. Chapters discussing each of the endocrine organs and their hormones and diseases have been revised. The endocrine aspects of metabolic bone disease, growth, sexual differentiation, pregnancy, obesity, lipoproteins, and AIDS, as well as the special problems of geriatric patients and endocrine emergencies, have all been brought up to current practice standards. In this edition there are several new chapters. There is a new and comprehensive review of female reproductive endocrinology and infertility, emphasizing the physiology of the female reproductive system and the management of female endocrine problems and infertility. The new chapter on the adrenal medulla includes a scholarly review of the diagnosis and management of pheochromocytomas. A new chapter on endocrine surgery reviews the indications for and results of operation in patients with endocrine diseases. In these times of information overload, a concise, authoritative, and readable text dealing with the function and malfunction of the human endocrine system is of extraordinary value. We believe it will be especially helpful to clinicians dealing with endocrine problems in patients, to researchers who wish to review a particular area of hormonal physiology, to medical students, residents, and endocrinology fellows training in this field, and to nurses responsible for patient care. We are proud to continue the tradition of excellence established in previous editions of this text